2017
DOI: 10.1021/acsnano.7b01087
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes Mediate Epithelium–Mesenchyme Crosstalk in Organ Development

Abstract: Organ development requires complex signaling by cells in different tissues. Epithelium and mesenchyme interactions are crucial for the development of skin, hair follicles, kidney, lungs, prostate, major glands, and teeth. Despite myriad literature on cell–cell interactions and ligand–receptor binding, the roles of extracellular vesicles in epithelium–mesenchyme interactions during organogenesis are poorly understood. Here, we discovered that ~100 nm exosomes were secreted by the epithelium and mesenchyme of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(82 citation statements)
references
References 40 publications
1
81
0
Order By: Relevance
“…We speculate that this effect comes from the specific exosomal cargo, as the UBtip-derived exosomes contain many proteins related to tissue morphogenesis and homeostasis as discussed above and miRNAs upregulating the Wnt pathway and increasing cell survival. Moreover, miR-135a, which we found highly upregulated in the UBtip-derived exosomes (Figure 3(e)), has already been shown to play an important role in activating the Wnt/β-catenin pathway in tooth mesenchyme differentiation [9]. In the renal MM, it may have the same effect, but this remains to be investigated in further detail.…”
Section: Resultsmentioning
confidence: 78%
“…We speculate that this effect comes from the specific exosomal cargo, as the UBtip-derived exosomes contain many proteins related to tissue morphogenesis and homeostasis as discussed above and miRNAs upregulating the Wnt pathway and increasing cell survival. Moreover, miR-135a, which we found highly upregulated in the UBtip-derived exosomes (Figure 3(e)), has already been shown to play an important role in activating the Wnt/β-catenin pathway in tooth mesenchyme differentiation [9]. In the renal MM, it may have the same effect, but this remains to be investigated in further detail.…”
Section: Resultsmentioning
confidence: 78%
“…In addition to communication between the mother and fetus, exosomes also mediate the crosstalk between the epithelium and mesenchyme, thus playing a crucial role in organ development. Epithelial and mesenchymal exosomes were preferentially adsorbed by reciprocal cell types in a developing tooth and reciprocally induced cell differentiation and matrix synthesis 101 . Moreover, a recent study has shown that keratinocyte-secreted exosomes are capable of enhancing melanin synthesis, revealing an unforeseen function of exosomes in human pigmentation 102 .…”
Section: Physiological Roles Of Exosomesmentioning
confidence: 99%
“…When Rab27a/b knockdown was used to disrupt exosome biosynthesis, enamel and dentin formation was reduced in organ culture experiments. Accordingly, the investigators further identified miR135a as an exosome component influencing Wnt signaling that increased dentin matrix protein expression (Jiang et al, 2017). Another recent study demonstrated exosome miRNA regulation of apoptosis in tooth development where the upregulation of miR133b -induced apoptosis in primary dentin mesenchyme and its ectopic expression prevented proper experimental tooth formation .…”
Section: Msc Exosome Roles In Oral and Craniofacial Tissue Engineeringmentioning
confidence: 98%